Synthesis of Silicon Nitride by Mechanical Alloying and Heat Treatment - M. Khajelakzay; S. R. Bakhshi; G.H. Borhani (Journal of Advanced Materials in Engineering, 2016)
In this study, synthesis of silicon nitride by mechanical alloying and the effects of important parameters of milling time and heat treatment temperature, time and rate are presented. Silicon micro powder and nitrogen gas were used as precursor materials. Synthesized phases, morphology and particle size were investigated by X-ray diffraction pattern (XRD) and Field emission scanning electron microscopy (FE-SEM), respectively. X-ray fluorescence analysis (XRF) was used for silicon nitride purity investigation.The optimum sample was produced at 30 h milling time, heat treatment at 1300 ℃ and 22 ℃/min heating rate conditions. X-ray fluorescence analysis showed more than 98% purity.